Pengalaman ODHA Mengikuti Terapi Mindfulness Spritual - Yuliana, Yuliana; Kusuma, Ratu; Pebrianti, Dwi Kartika; Dwiyanti, Rahmi (Jurnal Akademika Baiturrahim Jambi, 2024)
ODHA are people with HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immuno Deficiency Syndrome). Changes in the character of ODHA cannot be separated from psychological and social pressures and make many ODHA become depressed. Psychological and social pressure experienced by ODHA also has a negative impact so that ODHA becomes embarrassed, physically exhausted, limits activities, fears, and does not know what to do in the future. awareness of ODHA. In addition, the therapy carried out has not been independent of PLWHA to be able to handle the problems experienced in the long term. To overcome this problem, an intervention aimed at ODHA Mindfulness therapy. Mindfulness as a psychotherapy facilitated by nurses using the concept of self-care theory where nurses become nursing agencies to facilitate self-deficit experienced by ODHA who have mental problems. This research is a qualitative research method that aims to see the experience of ODHA following spiritual mindfulness therapy. This research will be conducted at the Putri Ayu Health Center Jambi in September 2021-August 2022. The results of this study were obtained after spiritual mindfulness therapy was carried out, the keywords were participants felt relieved, calm, comfortable, the burden on the mind, the burden on the chest, the burden on the shoulders felt reduced and disappeared.